High sensitivity cardiac troponins: Can they help in diagnosing myocardial ischaemia?. Issue 6 (1st September 2018) - Orsini, Enrico; Caravelli, Paolo; Dini, Frank Lloyd; Marzilli, Mario
Abstract: Background: Cardiac troponin is the most sensitive marker of myocardial injury, but controversy still exists about its role in detecting ischaemia. Methods: To investigate the role of troponin as a marker of stress-induced ischaemia, circulating high sensitivity cardiac troponin T (hs-cTnT) was measured and compared with the MB fraction of creatine kinase (CK-MB) in 125 patients undergoing a stress test (53 electrocardiogram/echo exercise, 42 echo dipyridamole and 30 echo dobutamine tests). Results: Plasma concentrations of hs-cTnT increased after the tests in 90/125 patients, while an increase of CK-MB was seen in 31/125 patients ( p <0.0001). Overall, hs-cTnT significantly increased from 17.5±16.9 ng/l to 25.5±27.9 ng/l ( p <0.0001), without significant changes of CK-MB. Significant increments in hs-cTnT were documented after exercise test (from 15.9±11.9 ng/l to 19.5±13.6 ng/l, p <0.0001) and dobutamine test (from 20.6±20.8 ng/l to 37.8±31.1 ng/l, p =0.0006), in absence of changes in CK-MB according to each stressor. Among the 125 tests, 84 were diagnosed as negative and 41 as positive for myocardial ischaemia. Significant increments in hs-cTnT were detected after both negative (from 18.6±19.2 ng/l to 27.1±32.1 ng/l, p =0.0018) and positive test (from 15.2±10.8 ng/l to 22.3±16.2 ng/l, p =0.0005), without significant changes of CK-MB according to the test result. Despite a positive correlation between stress-induced increase of hs-cTnT and obstructive coronary artery disease, the release of troponin was observed also in a significant proportion of patients without coronary stenoses. Left ventricular hypertrophy markedly enhanced myocardial release of troponin. Conclusions: Circulating troponin increases in most patients undergoing a stress test, irrespective of the test result and of coronary artery disease. Plasma release of troponin depends on multiple pathogenetic mechanisms, making the biomarker a not reliable tool in detecting transient ischaemia.